2005
DOI: 10.1007/s10072-005-0440-7
|View full text |Cite
|
Sign up to set email alerts
|

Stroke units and general wards in seven Italian regions: the PROSIT Study

Abstract: PROSIT (research PROject on Stroke services in ITaly) is a study performed to evaluate number and work organisation of acute in-hospital services (stroke units, SU) and general wards (GW), in seven Italian regions (Liguria, Lombardia, Lazio, Veneto, Friuli-Venezia-Giulia, Emilia Romagna, Toscana), which have a population of 29 169 811 inhabitants and a relative ratio of 225/100 000 hospitalisations for acute stroke. The registers of hospital discharges from January to December 1999 were looked at identify to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
1
9
0
2
Order By: Relevance
“…All SUs reported that they have multidisciplinary meetings and practice early rehabilitation. These findings, compared with our previous survey [13,14], show the tendency in Italy to increase the number and the quality of structures dedicated to stroke care. Nevertheless, the study demonstrated an overall shortage of stroke unit beds, which was clearer in the central and southern parts of the country.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…All SUs reported that they have multidisciplinary meetings and practice early rehabilitation. These findings, compared with our previous survey [13,14], show the tendency in Italy to increase the number and the quality of structures dedicated to stroke care. Nevertheless, the study demonstrated an overall shortage of stroke unit beds, which was clearer in the central and southern parts of the country.…”
Section: Discussionsupporting
confidence: 52%
“…A shortage of acute SU beds is also evident in many European countries where the percent of stroke patients hospitalised in a SU bed ranged from 5% to 40%. Access to SUs is quite good in Norway [18], Sweden [19], Germany [20], Austria [21] and Scotland [22], but is still patchy in France [23], Hungary [24], Italy [13,14], Poland [25] and Portugal [26]. In Australia only 23% of hospitals had a SU [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The factors influencing quality service provision are likely to be different in each. The availability of the most effective intervention (coordinated stroke unit care 18 ) remains limited, reflecting results from recent large-scale national 19,20 and international 5,21 studies.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Limitations in procedural accessibility and nursing care availability further prohibit more complicated methods to reduce fever, highlighting the need for a safe, simple and cost-effective cooling strategy for stroke patients, particularly those non-critically ill admitted to the regular ward. [15][16][17] Based on clinical observations and theoretical cooling analyses, [18][19][20] we were interested in whether intravenous (IV) infusions of chilled crystalloid or designer ice slurry/ saline solutions, adjusted for safety and efficiency to daily fluid requirements and temperature fluctuations, would conveniently and inexpensively control fever. Intravenous fluids are routinely administered to patients with cerebrovascular events to stabilize intravascular volume and improve systemic cardiovascular function and brain perfusion.…”
Section: Introductionmentioning
confidence: 99%